Nitration and amination of polyphenylene oxide: synthesis, gas sorption and permeation analysis - Bhole, Yogesh S.; Karadkar, Prasad B.; Kharul, Ulhas K. (European Polymer Journal, 2007)
A high degree of nitration of polyphenylene oxide (PPO) was successfully achieved by carefully optimizing synthetic protocol. The reduction of nitro group to amino could be done quantitatively. The physical properties of formed polymers were investigated and correlated with gas sorption and permeation properties. The formed polymers were amorphous in nature as revealed by wide angle X-ray diffraction spectra. An increase in the packing density in comparison to unsubstituted PPO as a result of induced polarity was indicated by lowering of fractional free volume and d-spacing. The substitution by either nitro or amino group increased the chain stiffness as revealed by the dynamic mechanical analysis. Though both, nitro and amino group substitution on PPO led to a decrease in pure gas permeability, the selectivity of various gas pairs was increased by these substitutions. The gas sorption analysis revealed that both, solubility selectivity and diffusivity selectivity were increased by these polar group substitutions. The nitro group substitution was more effective in improving solubility selectivity, while amino group substitution was more effective in improving diffusivity selectivity. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Amination; nitration; permeation; polyphenylene oxide; Sorption

N-substitution of polybenzimidazoles: synthesis and evaluation of physical properties - Kumbharkar, Santosh C.; Kharul, Ulhas K. (European Polymer Journal, 2009)
Series of N-substituted polybenzimidazoles (PBI) were synthesized using selective alkyl groups with varying bulk and flexibility, viz., methyl, n-butyl, methylene trimethylsilane and 4-tert-butylbenzyl. PBl-I based on 3,3'-diaminobenzidine (DAB) and isophthalic acid and PBI-Bul based on DAB and 5-tert-butyl isophthalic acid were chosen for N-substitution. Structural characterizations of substituted polymers by FT-IR and (1)H NMR revealed elimination of hydrogen bonding. Evaluation of their physical properties revealed that N-substitution rendered better solvent solubility in common organic solvents, more open polymer matrix, but reduced thermal properties in comparison to their respective parent PBI. 4-tert-butylbenzyl, methylene trimethylsilane or n-butyl group substituted polymers were soluble even in chlorinated solvents (CHCl(3) and TCE). Substantial variations in gas permeability of inert gases, He and Ar and attractive P(He)/P(Ar) selectivity, especially after methyl group substitution depicted potential of these materials for gas separation. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Gas permeation; hydrogen bonding; N-Substitution; Polybenzimidazole

New N-substituted ABPBI: synthesis and evaluation of gas permeation properties - Kumbharkar, Santosh C.; Kharul, Ulhas K. (Journal of Membrane Science, 2010)
Aromatic poly(2,5-benzimidazole), ABPBI was post-modified for the first time to produce organosoluble N-substituted ABPBI. This modification was carried out by N-substitution of ABPBI with bulky alkyl groups, viz., 4-tert-butylbenzyl and methylene trimethylsilyl in an attempt to utilize high rigidity of ABPBI towards gas permeation. These substituted polymers exhibited solubility in common organic solvents, enhancing their processability than ABPBI, which is soluble only in acidic solvents. Considerable decrease in chain packing density led to increase in gas sorption as that of unsubstituted ABPBI. The permeability of pure gases of commercial significance (He, H(2), N(2), O(2), CH(4) and CO(2)) were high, coupled with attractive selectivities. In comparison to conventional PBI, methylene trimethylsilyl substituted ABPBI led to considerably high (33 folds) CO(2) permeability with almost similar selectivity (P(CO2)/P(N2) approximate to 33). Feasibility of these N-substituted ABPBIs to be converted in to required membrane form along with its considerably higher permeation properties depicted the potential of this polymer to be used as gas separation material. Gas diffusion coefficients were estimated from solubility and permeability coefficient. These, along with dual-mode sorption parameters estimated from sorption isotherms provided an insight towards variations in permeation behavior caused by the substitution. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: 5-benzimidazole); Diffusion; Gas permeation; N-Substitution; Poly(2; Sorption

New approach of blending polymeric ionic liquid with polybenzimidazole (PBI) for enhancing physical and electrochemical properties - Rewar, Anita S.; Chaudhari, Harshal D.; Illathvalappil, Rajith; Sreekumar, K.; Kharul, Ulhas K. (Journal of Materials Chemistry A, 2014)
Although the use of ionic liquids (IL) in polymeric membranes is known to elevate the electrochemical performance for proton exchange membrane-based fuel cells (PEMFC), they suffer from drawbacks such as IL drain and lowering in mechanical properties that lead to deterioration in PEMFC performance. To mitigate these issues, we report, for the first time, the use of polymeric ionic liquid (PIL), namely, poly(diallyl dimethyl ammonium trifluoride methane sulphonate) (P[DADMA][TFMS]) to be blended with polybenzimidazole (PBI-I) as a membrane material for PEMFC. PBI-I and (P[DADMA][TFMS]) were chosen because they form miscible blends and are suitable for acid doping as a matrix, which can eventually be used as proton conductor. The structure, miscibility and inter-polymer interactions were studied by infrared (IR) spectroscopy and differential scanning calorimetry (DSC). The increase in proton conduction in comparison to the PBI membranes was observed due to the presence of ionic groups of PILs in blend membranes. With the increase in PIL content, the proton conductivity of the composite membranes gradually increased from 0.04 S cm(-1) for PBI to 0.07 S cm(-1) for the blend membrane at 150 degrees C. The MEAs were fabricated with PBI-I, PBI-PIL15, PBI-PIL25 and PBI-PIL35. Corresponding single cells were successfully tested at temperatures of 160 degrees C. The maximum power density and current density obtained were 515 mW cm(-2) and 1632 mA cm(-2), respectively, for PBI-PIL25-based MEA.